Systematic Identification of Plasmodium Falciparum Sporozoite Membrane Protein Interactions Reveals an Essential Role for the p24 Complex in Host Infection - Knöckel, Julia (Mol Cell Proteomics, 2021)
Sporozoites are a motile form of malaria-causing Plasmodium falciparum parasites that migrate from the site of transmission in the dermis through the bloodstream to invade hepatocytes. Sporozoites interact with many cells within the host, but the molecular identity of these interactions and their role in the pathology of malaria is poorly understood. Parasite proteins that are secreted and embedded within membranes are known to be important for these interactions, but our understanding of how they interact with each other to form functional complexes is largely unknown. Here, we compile a library of recombinant proteins representing the repertoire of cell surface and secreted proteins from the P. falciparum sporozoite and use an assay designed to detect extracellular interactions to systematically identify complexes. We identify three protein complexes including an interaction between two components of the p24 complex that is involved in the trafficking of glycosylphosphatidylinositol-anchored proteins through the secretory pathway. Plasmodium parasites lacking either gene are strongly inhibited in the establishment of liver-stage infections. These findings reveal an important role for the p24 complex in malaria pathogenesis and show that the library of recombinant proteins represents a valuable resource to investigate P. falciparum sporozoite biology.